Acknowledging the value of friendships and relationships in supporting personal and professional development. Issue 2 (4th May 2022) - Smith, Sara; Braszkiewicz, Wiktoria; Goncalves Barbosa Neto, Carolina; Mohammed, Bothyna; McCulla, Daniel; Khechara, Martin
ABSTRACT: Covid-19 has driven a move away from face-to-face learning and time spent on campus for all university students. This study explores social restrictions through the lens of friendships and creation of meaningful relationships for students from a widening participation (WP) background embarking upon a Medicine with Foundation Year programme. Previous studies highlight the importance of meaningful interactions in facilitating students' personal and professional development and highlight how students from WP backgrounds often struggle forming advantageous relationships at university, missing opportunities to increase their social capital during the crucial first few years at medical school. An exploratory approach was adopted for this collaborative study to understand the impact of upon students' lived experiences and the development of advantageous relationships. Although this is a small cohort study, and too limited for generalisations, it provides valuable insight into the negative impact of restrictions on friendships and relationship building. It highlights the value of embedding opportunities for informal interactions, networking and social activities into university programmes to enable the nurturing of relationships and friendships. As we move into a post-COVID-19 era it calls for further research into the impact of behavioural changes on communities of practice and learning through formal and social interactions.